Religion and Medicine, Again: JHMAS Commentary on "The Lourdes Medical Cures Revisited" - J. Duffin (Journal of the History of Medicine and Allied Sciences, 2014)
In 1993, Foster Care Youth United published its first issue. A magazine written for and by teens in foster care, it reflected many of their key concerns of the moment. Teens wrote poignantly of abuse, separation, sexual exploitation at group homes, and the difficulties of "aging out of the system." The children's pain was palpable; Foster Care Youth United gave them a voice. Charlie Rose interviewed some of these foster youth, giving them a broad audience and national attention. This essay examines a moment in the early 1990s when young people in foster care developed a powerful voice that resonated throughout the country. Yet at the very same time, as Congress debated a law that would affect these teens' lives, their voices were not heard. Instead, numerous witnesses averred that they were speaking on behalf of children. This essay reconstructs the voices of the foster youth themselves as they shared their experiences and thoughts in their new magazine. It asks why these voices were absent from the contemporary debates preceding the passage of the 1997 Adoption and Safe Families Act (ASFA), and compares the use of their voices in debates around the 1999 Foster Care Independence Act.